VALUES IN THE FAMILY THAT AFFECT THE YOUTH CHARACTER HABITUATION WITH THE MOTHER WORK - Dian Pertiwi Josua; Euis Sunarti; Diah Krisnatuti (Jurnal Pendidikan Karakter, 2019)
Character education can be applied through various methods, including the internalization of values and character habituation. The purpose of this study was to analyze the characteristics of adolescents and families, family values, and character habituation; analyze the influence of adolescent and family characteristics, family values, on habituation of adolescent characters. Respondents in this study were 200 people with translation; 100 junior and senior high school students in the Sukmajaya Depok area, and mothers of these teens who work. Location selection uses purposive, and respondents are selected by random sampling. The results of the analysis state that the highest family value internalized by working mothers in adolescents is the value of humility. Conversely, a low value is the value of family recognition through achievement. Another finding based on Partial Least Square analysis shows that family values that have a significant positive effect on adolescent character habituation are self-control and emotion (p=0.029, t1,96). While family values that have a significant negative effect are family recognition through achievement (p=0.000, t1,96), and humility (p=0.042, t1,96).